Persian Epic writing and its reflection in the Sindhi poetry of Tha’bit Ali Shah (The first Sindhi Elegy writer and his Epic writing in Ferdowsi’s Style) - Mirza, Faizeh Zehra (sourcecoder, 2024)
Sayyed Tha’bit Ali Shah is a renowned elegiac poet of the Kalhora and Talpur period who apart from being the first Sindhi poet to introduce elegy in Sindhi poetry, also wrote epic poetry in Ferdowsi's style. Due to the genius of writing elegies in the Sindhi language, he is considered as the greatest elegiac writer of the subcontinent and is called "Anis of Sindh". He wrote elegies and Sindhi poems based on Arabic and Persian prosody and used Persian words, similes, phrases, allusions and metaphors in Sindhi elegies, which were not common in Sindhi poetry before. He has decorated his poetry with allusions, Quranic verses and hadiths. Being influenced by Ferdowsi’s Shahnama, Tha’bit Ali Shah has written an Epic following the same meter and rhyme of Shahnama e Ferdousi regarding the war which took place between the Kalhora and Talpur rulers and has named it “Zafar Nameh”. This poem is one of his masterpieces in Persian language. Tha’bit Ali Shah visited Iran as an embassador of the Talpur rulers, and during his meeting with Fath Ali Shah Qajar, he presented two of his Persian odes which he had written in praise of the Shah of Iran. His odes were appreciated by Fath Ali Shah Qajar. This outstanding poet was proficient in Saraiki, Sindhi, Urdu, Persian and Arabic languages, and his poems are praiseworthy in all four languages.